FROM BATTLEFIELDS TO BENCHMARKS : TRACING THE PAST AND SHAPING THE FUTURE OF INTERNATIONAL HUMANITARIAN LAW - Tayewo Adewumi; Amade Roberts Amana (Khairun Law Journal, 2026)
The evolution of International Humanitarian Law (IHL) reflects humanity’s enduring quest to bring moral restraint to armed conflict. This paper explores the historical development of IHL, tracing its origins from early customary warfare codes and pivotal moments such as the Geneva Conventions, to contemporary legal frameworks responding to cyber warfare, autonomous weapons, and asymmetrical conflicts. By examining the influence of key actors—states, humanitarian organizations, and legal scholars—the study highlights the transformative milestones that have shaped IHL’s trajectory. Furthermore, it critically assesses present-day challenges, including enforcement mechanisms and the politicization of humanitarian principles. Looking forward, the paper proposes pathways for strengthening IHL amid emerging global threats, advocating for legal adaptability, inclusivity, and a recommitment to core humanitarian values. From ancient battlegrounds to modern policy arenas, the evolution of IHL remains a testament to the resilience of law in protecting humanity’s conscience during war.